PCBs in the Arctic atmosphere: determining important driving forces using a global atmospheric transport model - Carey Friedman (Arctic Data Center, 2016)
We present a spatially and temporally resolved global atmospheric polychlorinated biphenyl (PCB) model, driven by meteorological data, that is skilled at simulating mean atmospheric PCB concentrations and seasonal cycles in the Northern Hemisphere midlatitudes and mean Arctic concentrations. However, the model does not capture the ob- served Arctic summer maximum in atmospheric PCBs. We use the model to estimate global budgets for seven PCB con- geners, and we demonstrate that congeners that deposit more readily show lower potential for long-range transport, consistent with a recently described "differential removal hypothesis" regarding the hemispheric transport of PCBs. Using sensitivity simulations to assess processes within, outside, or transport to the Arctic, we examine the influence of climate- and emissions-driven processes on Arctic concentrations and their effect on improving the simulated Arctic seasonal cycle. We find evidence that processes occurring outside the Arctic have a greater influence on Arctic atmospheric PCB levels than processes that occur within the Arctic. Our simulations suggest that re-emissions from sea ice melting or from the Arctic Ocean during summer would have to be unrealistically high in order to capture observed temporal trends of PCBs in the Arctic atmosphere. We conclude that midlatitude pro- cesses are likely to have a greater effect on the Arctic under global change scenarios than re-emissions within the Arctic.